Chloroquine and its derivatives exacerbate B19V-associated anemia by promoting viral replication. - Claudia Bönsch; Christoph Kempf; Ivo Mueller; Laurens Manning; Moses Laman; Timothy M E Davis; Carlos Ros (Public Library of Science (PLoS), 2010)
BACKGROUND: An unexpectedly high seroprevalence and pathogenic potential of human parvovirus B19 (B19V) have been observed in certain malaria-endemic countries in parallel with local use of chloroquine (CQ) as first-line treatment for malaria. The aims of this study were to assess the effect of CQ and other common antimalarial drugs on B19V infection in vitro and the possible epidemiological consequences for children from Papua New Guinea (PNG). METHODOLOGY/PRINCIPAL FINDINGS: Viral RNA, DNA and proteins were analyzed in different cell types following infection with B19V in the presence of a range of antimalarial drugs. Relationships between B19V infection status, prior 4-aminoquinoline use and anemia were assessed in 200 PNG children <10 years of age participating in a case-control study of severe infections. In CQ-treated cells, the synthesis of viral RNA, DNA and proteins was significantly higher and occurred earlier than in control cells. CQ facilitates B19V infection by minimizing intracellular degradation of incoming particles. Only amodiaquine amongst other antimalarial drugs had a similar effect. B19V IgM seropositivity was more frequent in 111 children with severe anemia (hemoglobin <50 g/L) than in 89 healthy controls (15.3% vs 3.4%; P = 0.008). In children who were either B19V IgM or PCR positive, 4-aminoquinoline use was associated with a significantly lower admission hemoglobin concentration. CONCLUSIONS/SIGNIFICANCE: Our data strongly suggest that 4-aminoquinoline drugs and their metabolites exacerbate B19V-associated anemia by promoting B19V replication. Consideration should be given for choosing a non-4-aminoquinoline drug to partner artemisinin compounds in combination antimalarial therapy.